31 The New National Institute for Health and Care Excellence (NICE) TA314 Guidelines may have a Significant Impact on Implantable Cardioverter Defibrillator (ICD) and Cardiac Resynchronisation Therapy (CRT) Implant Rates in District General Hospitals. (6th June 2015) - Mahendiran, Thabo; Gosling, Oliver; Newton, Judith; Giblett, Dawn; McKenzie, Dan; Dayer, Mark
Abstract : Implantable cardiac electronic devices have revolutionised the management of heart failure in patients with a reduced ejection fraction, already on optimal medical therapy. In June 2014 the National Institute for Health and Care Excellence (NICE) released new guidelines (TA314) regarding implantable cardioverter defibrillator (ICD) and cardiac resynchronisation therapy (CRT) devices, updating and amalgamating previous guidelines (TA95 and TA120) that were released in January 2006 and May 2007 respectively. These new guidelines have broadened the indications for device implantation. We undertook an audit to investigate the impact of the new NICE guidelines on the potential implant rates of ICDs and CRT devices in patients diagnosed with heart failure. The clinical records of 396 consecutive patients admitted to hospital by the nurse-led heart failure service between 01/01/2013 and 15/08/2014 were reviewed. 48 patients died during their admission, 60 had no recorded ejection fraction, and 22 had an existing device and were excluded from further analysis. 291 patients were included in the analysis (Table 1). Applying the NICE TA95 and TA120 guidelines, a total of 46 devices were indicated: 10 ICDs, 25 CRT-P devices and 11 CRT-D devices. Applying the NICE TA314 guidelines, a total of 122 devices were indicated: 53 ICDs, 24 CRT-P devices and 45 CRT-D devices (Table 2). The 53 ICDs indicated by the new guidelines included patients with a left ventricular ejection fraction ≤35%, QRS duration <120 milliseconds and a New York Heart Association class of I-III, who would be eligible for an ICD under our local policy due to high risk of sudden cardiac death. These findings suggest that a further 76 devices would be indicated under the new NICE TA314 guidelines which is a highly significant increase, p < 0.0001 (Fisher's exact test). This represents a potential extra 47 devices per annum. The additional 76 devices recommended by the 2014 guidelines corresponded mainly to an increase in the number of ICD and CRT-D devices, which represent the more expensive and technically challenging systems to instal. The estimated cost of the 46 devices recommended by the NICE TA95 and TA120 guidelines was £317, 418. The estimated cost of the 122 devices recommended by the NICE TA314 guidelines was £1, 148, 725. This represented a potential £831, 307 increase in spend on implantable cardiac devices over the study period. In conclusion, the new NICE guidelines for device therapy look set to significantly increase the number of patients for whom an implantable cardiac device is indicated. This has significant financial implications at both a local and national level, as well as consequences for workforce planning and training.